Harmonious workplace climate and employee altruistic behavior: from social exchange perspective. Issue 1 (30th May 2020) - Bui, Hong T.M.; Liu, Gordon; Ko, Wai Wai; Curtis, Amy
Abstract : Purpose: Drawing on the social exchange perspective, the authors explore the roles of satisfaction over material rewards, perceived organizational politics and career ambition in the relationship between harmonious workplace climate and employee altruistic behavior in the context of British public sector. Design/methodology/approach: The authors employed SPSS software to estimate ordinary least squares models to test their hypotheses by analyzing data from 161 supervisor–employee dyads from a UK local government. Findings: Satisfaction over material rewards mediates the relationship between harmonious workplace climate and employee altruistic behavior. Both perceived organizational politics and career ambition moderate the mediated effect of harmonious workplace climate on employee altruistic behavior via satisfaction over material rewards. Originality/value: This study advances the social exchange theory by showing that the norm of reciprocity (e.g. harmonious workplace climate in this study) may not be the only key driver of exchange for altruistic behavior among public sector workers. Still, it can be mediated by satisfaction with pay and promotion opportunities and may be conditional upon individuals' career ambition or their perceptions of organizational politics.